Vulnerability and Shame in the Writing of the Female Body: Emilie Pine’s Notes to Self - Lucía Bennett-Ortega (Revista Alicantina de Estudios Ingleses)
This article examines the representation of the female body in Emilie Pine’s (2018) personal essay ‘Notes on Bleeding & Other Crimes.’ Drawing on vulnerability studies and feminist criticism, I argue that the vulnerability and shame surrounding women’s bodies are reframed as agentic forces, motivating Pine to craft a distinctly feminist narrative. Through a confessional and feminist style that resonates with French feminists’ concept of “écriture féminine,” Pine’s writing transforms personal experience into political critique. The first part of the analysis is dedicated to the representation of the body and its vulnerability, especially in relation to the bodily elements of menstruation and scars. More specifically, I make use of Elaine Scarry’s (1985) formulation of the stages of the “projection of the body,” to examine the journey Pine undergoes in the conceptualisation of her own body: from being ashamed to unashamed. The second part of the analysis explores how Pine’s style of writing leads to the reclaiming of the female body along the lines of what Hélène Cixous (1976) advocates in her influential essay ‘The Laugh of the Medusa.’ Ultimately, Pine’s text illustrates a reconfiguration of vulnerability – not as something negative, but as a source of potential and resistance.